Caffeine and alcohol as risk factors for sudden infant death syndrome. Issue 2 (1st August 1999) - Alm, B; Wennergren, G; Norvenius, G; Skjærven, R; Øyen, N; Helweg-Larsen, K; Lagercrantz, H; Irgens, L M
Abstract : OBJECTIVE: To assess whether alcohol and caffeine are independent risk factors for sudden infant death syndrome (SIDS). MATERIALS AND METHODS: Analyses based on data from the Nordic epidemiological SIDS study, a case control study in which all parents of SIDS victims in the Nordic countries from 1 September 1992 to 31 August 1995 were invited to participate with parents of four controls, matched for sex and age at death. Odds ratios (ORs) were calculated by conditional logistic regression analysis. RESULTS: The crude ORs for caffeine consumption > 800 mg/24 hours both during and after pregnancy were significantly raised: 3.9 (95% confidence interval (CI), 1.9 to 8.1) and 3.1 (95% CI, 1.5 to 6.3), respectively. However, after adjustment for maternal smoking in 1st trimester, maternal age, education and parity, no significant effect of caffeine during or after pregnancy remained. For maternal or paternal alcohol use, no significant risk increase was found after adjusting for social variables, except for heavy postnatal intake of alcohol by the mother, where the risk was significantly increased. CONCLUSIONS: Caffeine during or after pregnancy was not found to be an independent risk factor for SIDS after adjustment for maternal age, education, parity, and smoking during pregnancy. Heavy postnatal but not prenatal intake of alcohol by the mother increased the risk.